Multiple paleopathologies in the dinosaur Bonitasaura salgadoi (Sauropoda: Titanosauria) from the Upper Cretaceous of Patagonia, Argentina - González, Romina (2017)
Bones in the fossil record sometimes exhibit unusual structures that can be attributed to pathologies, taphonomic alterations, or morphological variation. The goal of this work is to describe three bone abnormalities present in the type specimen of Bonitasaura salgadoi from the Cretaceous of north Patagonia, Argentina. The studied material corresponds to a left femur, a left metatarsal III, and a right prezygapophysis of a mid-caudal vertebra. Macroscopic and/or histological examinations were conducted, and a discussion concerning the origin of each abnormality is provided. The results of this study suggest that the anomalous structures are pathologies. In the femur, an osteoblastic tumor was identified by the presence of a large outgrowth of ovoid appearance with a spiculated microstructural pattern. The metatarsal III shows an enthesophyte (or bone spur) based on its location, shape and growth in parallel to the long axis of the bone element. Finally, the abnormal tissue observed in the prezygapophysis of the caudal vertebra was determined to be an infection by the presence of reactive new bone associated with a local widening of the subperiosteal margin and a sinus of drainage. This is the first report of multiple pathologies in a single specimen of a titanosaur, and it provides new insights about paleopathologies in sauropod dinosaurs.